Peranan Tingkat Pendidikan dan Diklat Terhadap Disiplin Kerja Pegawai Pada Dinas Sosial dan Tenaga Kerja Kabupaten Aceh Barat Daya - Hamzali, Said (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study was to determine the role of education level and training simultaneously on employee work discipline at the Social and Manpower Office of Aceh Barat Daya Regency, to determine the effect of education level on employee work discipline at the Social and Manpower Office of Aceh Barat Daya Regency and to determine the effect of training on employee work discipline at the Social and Manpower Office of Aceh Barat Daya Regency. This study was conducted at the Social and Manpower Office of Aceh Barat Daya Regency, while the object of this study was the level of education, and training and employee work discipline, with a total of 33 respondents. The results of the study showed that the level of education and employee training had a positive and significant effect on the variable of work discipline at the Social and Manpower Office of Aceh Barat Daya Regency. Then the results of the study also proved that partially the level of education had a positive and significant effect on the variable of employee work discipline of 0.180 at the Social and Manpower Office of Aceh Barat Daya Regency, and the training variable also had a positive and significant effect on the variable of employee work discipline of 0.190 at the Social and Manpower Office of Aceh Barat Daya Regency. After conducting this research, the Social and Manpower Service of Southwest Aceh Regency must be able to improve employee work discipline through the employee training program and should be a concern for the leadership, because in this research the education program has a significant effect on improving work discipline, so that work discipline becomes even better.